2020
DOI: 10.1016/j.cub.2019.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Branching Regulator BRC1 Mediates Photoperiodic Control of Seasonal Growth in Hybrid Aspen

Abstract: Highlights d BRANCHED 1 (BRC1) is a photoperiodically controlled seasonal growth regulator d BRC1 interacts with and antagonizes FLOWERING LOCUS T (FT) in hybrid aspen d BRC1 is a component of a negative feedback loop controlling seasonal growth

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 23 publications
4
49
0
1
Order By: Relevance
“…In WT, marker genes for ABA were induced in SD (Fig. 3b, columns 5-7) consistently with observations in other species that ABA signalling is induced in SD and is associated with bud dormancy 17,32,[35][36][37] . By contrast, BRC1b RNAi buds displayed a reduced ABA response relative to the WT in SD (Fig.…”
Section: Potato Brc1b Prevents Aerial Bud Tuberisation To Further Ansupporting
confidence: 86%
“…In WT, marker genes for ABA were induced in SD (Fig. 3b, columns 5-7) consistently with observations in other species that ABA signalling is induced in SD and is associated with bud dormancy 17,32,[35][36][37] . By contrast, BRC1b RNAi buds displayed a reduced ABA response relative to the WT in SD (Fig.…”
Section: Potato Brc1b Prevents Aerial Bud Tuberisation To Further Ansupporting
confidence: 86%
“…Previous research has demonstrated that BRC1 physically interacts with FT2, and BRC1-FT interaction triggers growth cessation by antagonizing FT action (Maurya et al, 2020). Some studies also indicated that BRC1 interacted with FT and TSF (TWIN SISTER OF FT) to regulate the activity of florigen in axillary buds and prevented the premature flowering transformation of axillary meristems (Niwa et al, 2013;Li et al, 2019).…”
Section: Roles Of Vctcp18 Gene In the Release Of Blueberry Flower Bud Dormancymentioning
confidence: 98%
“…FT2 downregulation results in inhibition of the expression of the downstream components LAP1 (the homologous gene of APETALA1 , a characteristic gene of Arabidopsis floral meristem) and AIL1 (the homologous gene of AINTEGUMENTA in Arabidopsis), which in turn eventually leads to growth cessation and bud formation 12 14 . Recent studies have shown that in addition to the CO/FT pathway, BRC1 (homologous to Arabidopsis gene BRANCHED 1 ) can form a feedback loop controlling seasonal growth in response to short days 15 (Fig. 2 ).…”
Section: Introductionmentioning
confidence: 99%